Transcriptome Analysis of Egg Yolk Sialoglycoprotein on Osteogenic Activity in MC3T3-E1 Cells - Sizhe He; Keke Meng; Muxue Chen; Lehui Zhu; Qingying Xiang; Zhangyan Quan; Guanghua Xia; Xuanri Shen (Applied Sciences, 2021)
In this study, the effects of egg yolk sialoglycoprotein (EYG) on osteogenesis in MC3T3-E1 cells were investigated and the DEGs (differentially expressed genes) were explored by transcriptome analysis. The results found that EYG effectively increased cell proliferation, enhanced ALP activity, promoted the secretion of extracellular matrix protein COL-I and OCN, enhanced bone mineralization activity, exhibiting good osteogenic activity. Further study of the mechanism was explored through transcriptome analysis. Transcriptome analysis showed that 123 DEGs were triggered by EYG, of which 78 genes were downregulated and 45 genes were upregulated. GO (gene ontology) analysis showed that EYG mainly caused differences in gene expression of biological processes and cell composition categories in the top 30 most enriched items. KEGG (Kyoto Encyclopedia of Genes and Genomes) analysis showed that EYG inhibited inflammatory factors and downregulated inflammation-related pathways. The results also showed EYG regulated such genes as COL2A1, COL4A1 and COL4A2 to up-regulate pathways including ECM–receptor interaction, focal adhesion and protein digestion and absorption, enhancing the proliferation and differentiation of osteoblasts. Gene expression of COL-I, Runx2, BMP2 and β-catenin was determined by qRT-PCR for verification, which found that EYG significantly increased COL-I, Runx2, BMP2 and β-catenin gene expression, suggesting that BMP-2 mediated osteogenesis pathway was activated.